PKM Optimalisasi Pelatihan Sistem Kontrol Pemberian Pakan, Vitamin dan Suhu Kandang bagi Kelompok Peternak Budidaya Ayam Ras Petelur di desa Gebangan Kraksaan Probolinggo - Tijaniyah; Alaika Nurir Robi; Ahmad Rifan Sauqi; Ahmad Jamil Sauqi (Jurnal Ilmiah Pengabdian dan Inovasi, 2022)
Cultivation of laying hens in the midst of the COVID-19 pandemic is very popular with the community as the main source of livelihood, the highest level of consumers is, they don't do a lot of activities outside the home and the profits are high. The comfort of the chicken coop, both in terms of feeding and the temperature of the cage, really needs to be considered because if the comfort of the cage runs effectively, the health of the chickens will be maintained and of course will produce more eggs. This can help the economy of laying hens breeders. So far, laying hens in the village of Gebangan Kraksaan Probolinggo still use the measurement of the temperature of the cage and conventional feeding, the temperature of the cage using lights, the number of cage guards who regulate the temperature and chicken feed so that honorarium costs also increase and do not use a certain time so that the number of chickens increases. less healthy than that, feeding is done alternately with farmers who take care of the feed so that it is not too late to give the feed. Therefore, a control system is very necessary in optimizing feeding and regulating the temperature of the cage automatically so that it can help laying hens breeders in the midst of the covid 19 pandemic to manage time, reduce the cost of house keeper fees and of course help the economic level of laying hens. Cultivation of laying hens in the midst of the COVID-19 pandemic is very popular with the community as the main source of livelihood, the highest level of consumers is, they don't do a lot of activities outside the home and the profits are high. The comfort of the chicken coop, both in terms of feeding and the temperature of the cage, really needs to be considered because if the comfort of the cage runs effectively, the health of the chickens will be maintained and of course will produce more eggs. This can help the economy of laying hens breeders. So far, laying hens in the village of Gebangan Kraksaan Probolinggo still use the measurement of the temperature of the cage and conventional feeding, the temperature of the cage using lights, the number of cage guards who regulate the temperature and chicken feed so that honorarium costs also increase and do not use a certain time so that the number of chickens increases. less healthy than that, feeding is done alternately with farmers who take care of the feed so that it is not too late to give the feed. Therefore, a control system is very necessary in optimizing feeding and regulating the temperature of the cage automatically so that it can help laying hens breeders in the midst of the covid 19 pandemic to manage time, reduce the cost of house keeper fees and of course help the economic level of laying hens.